Participatory Decision-Making and Teacher’s Job Performance in Public Secondary Schools - Adeseko Sunday Olaifa; Moses Adeleke Adeoye; Ebunlomo Oreoluwa Olaifa; Olubunmi Olufunke Oshin (Department of Guidance and Counseling, FIP, Undiksha, 2023)
The challenges faced by the teachers’ non-involvement in decision-making and the adverse effects on job performance are causes for concern. The study aims to analyze the participatory decision-making and teacher’s job performance in secondary schools. A descriptive survey of the correlational type was used for this study. Three research questions guided the study. A proportional random sampling technique was adopted to select 300 secondary school teachers from selected fifteen (15) secondary schools. The researcher's instrument used was titled “Participatory Decision-Making and Teachers’ Job Performance Questionnaires” (PDTJPQ) for data collection. The data was analysed using descriptive statistics of mean and standard deviation. The findings of this study indicate a positive correlation between participatory decision-making and teachers' job performance. Teachers who reported higher levels of involvement in decision-making processes demonstrated increased job satisfaction, motivation, and commitment to their work. Moreover, participatory decision-making was found to enhance teachers' sense of ownership, professional growth, and overall job effectiveness.